E-ASSESSMENT ASELIN BAGI PENYANDANG DISABILITAS - Saidacmajaya, Muhammad; Marlina, Marlina (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Technological advances are growing rapidly in today's modern era, but at this time there are still many campuses or universities that still use old methods to record their students, especially students with disabilities. This is a challenge for the campus in order to improve the performance and efficiency of the time used to record. Especially students with disabilities who are sometimes often neglected in terms of this data. Therefore, researchers formulated a solution by creating a website that can make it easier for agencies or campuses to record students with disabilities. By using the type of R&D (Research and Development) research and ADDIE development procedures, researchers developed a website called Aselin E-Assessment. There are 4 expert practitioners in this study, including (1) expert practitioners in the field of assessment, (2) expert practitioners in the field of websites, (3) expert practitioners in the field of special education and (4) expert practitioners in the field of children with special needs. Students of Padang State University who are disabled are the subjects of this research, and the quantitative descriptive data analysis technique is a combination that is in line with the way of thinking in this research. The results of this study indicate that the Aselin E-Assessment website is very feasible to use to record students with disabilities in college institutions.